Sowiecka cenzura jako narzędzie kontroli i represji wobec literatury rosyjskiej (1917–1929) - Ochniak, Magdalena (Slavia Orientalis, 2026)
Censorship is one of the many ways of limiting freedom of speech when an appropriate unit, organization or institution is created, whose main goal is to control the flow of information considered by the authorities to be undesirable, hostile or harmful. Censorship (understood both as print control and as the institution exercising this control) was always a tool in the hands of authorities, trying to prevent the dissemination of ideas and views harmful to the image of those in power. This was also the case in the USSR at the beginning of the 20th century, when the aim of literary censorship was not only to permanently control authors and readers, but, above all, to create an atmosphere of general fear related to the publication and reading of illicit texts, which was supposed to lead to a change in society’s way of thinking. This article shows how, at the beginning of its existence (1917‑1929), Soviet censorship gradually, and then on an increasingly wider scale, appropriated and destroyed subsequent areas of the functioning of literature: from limiting the circulation of books or paper allocation to a complete ban on printing, by eliminating already prepared book editions, withdrawing literature that was inconvenient to the authorities from libraries, closing publishing houses, censoring print runs, the content of works, or even the smallest pieces of information as to the existence of authors and their works.